Color Standardization Method and System for Whole Slide Imaging Based on Spectral Sensing - Shinsuke Tani; Yasuhiro Fukunaga; Saori Shimizu; Munenori Fukunishi; Kensuke Ishii; Kosei Tamiya (Analytical Cellular Pathology)
In the field of whole slide imaging, the imaging device or staining process cause color variations for each slide that affect the result of image analysis made by pathologist. In order to stabilize the analysis, we developed a color standardization method and system as described below: 1) Color standardization method based on RGB imaging and multi spectral sensing, which utilize less band (16 bands) than conventional method (60 bands), 2) High speed spectral sensing module. As a result, we confirmed the following effect: 1) We confirmed the performance improvement of nucleus detection by the color standardization. And we can conduct without training data set which is needed in conventional method, 2) We can get detection performance of H&E component equivalent to conventional method (60 bands). And measurement process is more than 255 times faster.